In‐Plane Black Phosphorus/Dicobalt Phosphide Heterostructure for Efficient Electrocatalysis. Issue 10 (5th February 2018) - Wang, Jiahong; Liu, Danni; Huang, Hao; Yang, Na; Yu, Bo; Wen, Min; Wang, Xin; Chu, Paul K.; Yu, Xue‐Feng
Abstract: Heterostructures composed of two‐dimensional black phosphorus (2D BP) with unique physical/chemical properties are of great interest. Herein, we report a simple solvothermal method to synthesize in‐plane BP/Co2 P heterostructures for electrocatalysis. By using the reactive edge defects of the BP nanosheets as the initial sites, Co2 P nanocrystals are selectively grown on the BP edges to form the in‐plane BP/Co2 P heterostructures. Owing to disposition on the original defects of BP, Co2 P improves the conductivity and offers more active electrocatalytic sites, so that the BP/Co2 P nanosheets exhibit better and more stable electrocatalytic activities in the hydrogen evolution and oxygen evolution reactions. Our work not only extends the application of BP to electrochemistry, but also provides a new idea to improve the performance of BP by utilization of defects. Furthermore, this strategy can be extended to produce other BP heterostructures to expand the corresponding applications. Abstract : In‐plane black phosphorus (BP)/Co2 P heterostructures were synthesized using the reactive edge defects of the BP nanosheets as the initial sites. Co2 P selectively grown on the BP edges improves the conductivity and offers more active electrocatalytic sites. The BP/Co2 P nanosheets exhibit a better and more stable electrocatalytic activity in hydrogen and oxygen evolution reactions.